ANALISIS KEUNGGULAN LIMONIT SOROAKO SEBAGAI KATALIS PENCAIRAN BATUBARA (DIRECT LIQUEFACTION) - Herman Hidayat; Lambok Hlarius Silalahi (Badan Pengkajian dan Penerapan Teknologi, 2007)
An investigation of catalytic activities of Soroako limonite ore using 1liter autoclavewas carried out. The comparison of the results with other iron catalysts forliquefaction of Banko coal was also performed to find out the best catalyst forBanko coal liquefaction. Much efforts to improve brown coal liquefaction processefficiency has been conducted at BPPT since 1994 through the design of highlyactive catalysts along with design of good hydrogen donor solvents. Someprevious studies have shown that limonite ore has several superior characteristicscompared to pyrite (FeS2) when used as catalyst in coal liquefaction process. Onemain reason is that limonite ore contains both iron and nickel compound asFeOOH, FeNi2OOH, FeCr2OOH that found to be responsible of high distillate.The use of natural ore for catalyst will implies that the production of industrialcatalyst for coal liquefaction could be obtained with low production cost. Theresults suggest that catalytic activity of Soroako limonite could be achieved at lowtemperature around 300 oC or less changing its crystallite form to pyrrhotite (Fe1-xS) species. Such phenomenon is similar to that of highly active Yandi Yellowcatalyst. Moreover, Soroako limonite catalyst also gives higher oil yield withsmaller amount of hydrogen consumption compare to pyrite and Yandi yellowcatalysts. So it concludes that Soroako limonite has high catalytic activity, and itssoft physical nature makes it possible to be pulverized into sub-micron particlesize easily and economically. Soroako limonite, therefore, can be recommendedas one of the most suitable catalysts for commercial coal liquefaction plant to beconstructed in the future.Kata kunci: coal liquefaction, soroako limonite, ï§-FeOOH, pyrrhotite, limonitecatalyst